Implementation Of Linear Congruent Method in Online Exam Applications For SMK Students - Amrullah Amrullah; Al-Khowarizmi Al-Khowarizmi (Sean Institute, 2022)
The Pangeran Antasari Vocational High School (SMK Pangeran Antasari) Final Examination (UAS) is an activity that determines the success of a student in 2 semesters of educational activities. UAS performs better when each student's questions are displayed randomly, and the difficulty can be increased to make each student's answer different. There are 101 questions per subject in the question bank, but the system displays 40 questions for each student. The Linear Congruential Method (LCM) method randomly displays question data in the app and provides each student with a different type of question pack. Each student's UAS scores are stored in a database for subject teachers and students' academic performance. The test results for the actual student application are assigned a different set of questions for each computer the student uses. Randomization of questions for each computer used by students using the LCM method gives each student a level of difficulty, resulting in a random question package of up to 40 questions with a difficulty level of 82.5%. Because certain question numbers have the same questions, but it can be recommended to help the school in the process of UAS activities.